Causal Effects of Rheumatoid Arthritis, Ankylosing Spondylitis, Juvenile Idiopathic Arthritis on Psoriasis: A Mendelian Randomization Study - Cao Y; Zhou M; Xu T (Dove Medical Press, 2024)
Yongping Cao, Mengyun Zhou, Tianhong Xu Department of Dermatology, Hangzhou Third People's Hospital, Hangzhou City, Zhejiang Province, People's Republic of ChinaCorrespondence: Tianhong Xu, Department of Dermatology, Hangzhou Third People's Hospital, 38 West Lake Road, Hangzhou City, Zhejiang Province, People's Republic of China, Email tianhongxu2024@163.comBackground: It is well-documented that rheumatoid arthritis (RA), ankylosing spondylitis (AS), and juvenile idiopathic arthritis (JIA) often exhibit skin manifestations, with psoriasis typically occurring around the time of diagnosis. Thus, it is essential to investigate the potential causal relationship between these forms of arthritis and psoriasis.Methods: The OpenGWAS provided traitIDs for exposure factors (RA (bbj-A-74), AS (ebi-A-GCST005529), and JIA (finn-b-JUVEN-ARTHR)) and outcome (psoriasis, finn-b-L12-PSORIASIS). bbj-A-74 had 19,190 samples (9,739,303 SNPs), ebi-A-GCST005529 had 22,647 samples (99,962 SNPs), finn-b-JUVEN-ARTHR had 173,622 samples (16,380,296 SNPs), and psoriasis had 216,752 samples (16,380,464 SNPs). Initially, 57 RA SNPs, 25 AS SNPs, and 5 JIA SNPs were acquired. Causal links were explored via univariate Mendelian Randomization (UVMR) analysis, with sensitivity analyses ensuring reliability. Additionally, multivariate MR (MVMR) analysis was conducted to further estimate the effect of each exposure factor on psoriasis.Results: Significant causal links (P < 0.05, OR > 1) were found between bbj-A-74, ebi-A-GCST005529, finn-b-JUVEN-ARTHR, and finn-b-L12-PSORIASIS, indicating associations of RA, AS, and JIA with psoriasis. Sensitivity analyses ensured the reliability of these finding, showing no heterogeneity, horizontal pleiotropy, or SNP locus oversensitivity in UVMR results. Furthermore, MVMR analysis revealed AS and JIA as psoriasis risk factors, while RA showed non-significant protective effects. This suggests AS and JIA may contribute to psoriasis onset or exacerbation when coexisting.Conclusion: MR analyses were conducted to investigate the causal links between RA, AS, JIA, and psoriasis, enhancing our grasp of the underlying mechanisms of psoriasis.Keywords: causal links, openGWAS, sensitivity analyses, risk factors